2021
DOI: 10.3390/jof7050383
|View full text |Cite
|
Sign up to set email alerts
|

Colombian Essential Oil of Ruta graveolens against Nosocomial Antifungal Resistant Candida Strains

Abstract: Drug resistance in antifungal therapy, a problem unknown until a few years ago, is increasingly assuming importance especially in immunosuppressed patients and patients receiving chemotherapy and radiotherapy. In the past years, the use of essential oils as an approach to improve the effectiveness of antifungal agents and to reduce antifungal resistance levels has been proposed. Our research aimed to evaluate the antifungal activity of Colombian rue, Ruta graveolens, essential oil (REO) against clinical strain… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
57
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(60 citation statements)
references
References 53 publications
1
57
0
2
Order By: Relevance
“… 37 In addition, amphotericin B combined with Ruta graveolens essential oil has also shown synergistic effects against C. albicans and C. tropicalis in vitro. 36 These results suggest that these natural compounds might provide a new promising strategy against Candida infection in the future.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“… 37 In addition, amphotericin B combined with Ruta graveolens essential oil has also shown synergistic effects against C. albicans and C. tropicalis in vitro. 36 These results suggest that these natural compounds might provide a new promising strategy against Candida infection in the future.…”
Section: Discussionmentioning
confidence: 91%
“… 35–38 Some essential oils extracted from plants have displayed inhibitory effects on the growth and activity of common Candida isolates. 35 , 36 , 38 UOST5-NPS, a novel anticandidal azole agent based on essential oils, has been developed for the newly emerged Candida auris. 37 In addition, amphotericin B combined with Ruta graveolens essential oil has also shown synergistic effects against C. albicans and C. tropicalis in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Essential oils are well-known for their bioactivities, e.g., antimicrobial and antioxidant, and have long been used in different traditional medicine systems as well as in modern medicine, cosmetics, and pharmaceutical products [ 29 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 ]. Their applications as an insecticidal, larvicidal, nematocidal, pesticidal, phytotoxic, and insect-repellent agents are also well-documented [ 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 ].…”
Section: Bioactivitiesmentioning
confidence: 99%
“…The essential oil of the aerial parts of R. graveolens exhibited antifungal activity against Melassezia furfur , which is usually found on the human skin and is responsible for skin diseases and dermatological conditions [ 88 ]. This essential oil was also active against several Candida species, namely, C. albicans (MIC 8.2 μg/mL), C. parapsilopsis (MIC 16.4 μg/mL), C. glabrata (MIC 4.1 μg/mL), and C. tropicalis (MIC 131.0 μg/mL) [ 89 ], and the plant pathogenic fungi Sclerotinia sclerotiorum (which causes white mold disease in plants) [ 90 ], Bipolaris oryzae , and Gerlachia oryzae [ 91 , 92 ].…”
Section: Bioactivitiesmentioning
confidence: 99%
“…Studies have shown that essential oils have the effect of resisting multi-drug resistant bacteria, including Candida tropicalis, Candida parapsilosis, Candida and trichomonas. [6][7][8] Geraniol is one of the representatives of acyclic isoprenoid monoterpenes, which can be separated from the essential oils of aromatic plants, including Cinnamomum tenuipilum, Valeriana officinalis and several other plants. 9 It was widely used in the food industry and medicine.…”
Section: Introductionmentioning
confidence: 99%